2016
DOI: 10.1007/s00405-016-4307-8
|View full text |Cite
|
Sign up to set email alerts
|

Work-up of globus: assessing the benefits of neck ultrasound and videofluorography

Abstract: Globus patients with normal ear, nose, and throat (ENT) status are a diagnostic challenge. The symptom may be long lasting and cause concern about malignancy, leading to possibly unnecessary further investigation. The aim of the study was to assess whether radiological examinations are useful in globus diagnostics, how often patients suffer from persistent globus, and whether globus patients with normal ENT status develop a malignancy during a follow-up. We reviewed medical records of all 76 globus patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…The main fear both in the patient, but also in the physician, is to overlook malignant disease; however, this is very rare in patients with monosymptomatic globus . No cases of malignant disease were discovered in our cohort.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The main fear both in the patient, but also in the physician, is to overlook malignant disease; however, this is very rare in patients with monosymptomatic globus . No cases of malignant disease were discovered in our cohort.…”
Section: Discussionmentioning
confidence: 61%
“…Järvenpää et al had a similar response rate and gender distribution in their questionnaire‐based follow‐up study but found a lower rate of persisting symptoms (62%) at 3‐year follow‐up, probably due to a longer study period …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although benign findings in barium swallow may be seen in globus patients, the causal relationship of these findings is questionable and hard to analyze in retrospective settings that the author mentioned [2,3]. Globus pharyngeus is a general symptom; it is usually intermittent, eating or drinking often helps and it has a great probability of resolving spontaneously, although the symptom recurs in some patients [4]. However, the before-mentioned findings in barium swallow are chronic conditions, such as osteophytes or Zenker's diverticulum, which may induce dysphagia symptoms rather than typical globus.…”
mentioning
confidence: 99%
“…Based on many studies, a typical globus pharyngeus without any alarming signs, such as progressive dysphagia, or findings in ear, nose, and throat examination, is not a sign of a malignancy [4,5]. To perform further investigations just to ensure the patient about the globus symptom's benign nature is not, however, justified.…”
mentioning
confidence: 99%